General domain ontology in enterprise software development process - Jabar, Marzanah A.; Khalefa, Mustafa S. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In software development, it is usually difficult to find the proper software component and customize or integrate it into the body of software. To reduce time and costs of errors produced in development processes, a systematically enriched representation of components is necessary. The main objective of this paper is to propose a general concept of domain ontology to express formally a shared understanding of information; we argue that they can be used to improve knowledge flow in enterprise software development process (SDP). In order to achieve this, we collect and analyse the concepts that have been used in knowledge flow ontology during enterprise software development process. We justify the need of the domain ontology in enterprise software development process. We further implemented the knowledge flow framework in domain ontology and validate it using a model of knowledge flow in software development. We performed a five-step procedure to measure the quality of the proposed knowledge flow framework model indicating that our proposed ontology for knowledge flow improves effectiveness of knowledge acquisition and sharing in software development organizations.